Oral history [videorecording] dialogue with living treasures of Philippine cinema - Keysor Fuji Cinema Film.; Mowelfund; Philippines. National Commission for Culture and the Arts. ([Manila] NCCA)
A documentation of the launching of the project. Includes interviews with noted personalities in Philippine cinema.
VHS.
Keywords: Motion-pictures -- History. -- Philippines; Motion pictures actors and actresses -- Philippines